Exploring the effectiveness of a novel memory training program for students with learning disabilities in the United Arab Emirates: investigating the role of gender differences - Alghazo, Emad; Abo Hamza, Eid; Bedewy, Dalia (Frontiers in Education, 2024)
The present research aims to investigate whether a newly developed memory training strategy may improve the memory of students with learning impairments. The research included thirty male and female students who had learning challenges. The students were assigned to resource rooms and divided into two groups: experimental and control. The control group did not undergo the training program, while the experimental group got a novel memory training program. Each group consisted of six male and nine female students. A technique for assessing recall was created based on previous studies. A measuring instrument was used to evaluate the memory of the participants before and after they finished the three-month training program. The study found statistically significant differences between the experimental and control groups in terms of the scores obtained on the novel memory scale (total score) and its aspects (Auditory, Visual, and Visual kinesthetic memory). The discrepancies were noted only among students in the experimental group who underwent the training program. Gender did not significantly affect the scores on the overall memory scale or its aspects, as shown by the findings. The interaction between gender and group did not have a statistically significant influence on training performance, indicating that both male and female students may benefit equally from this training. The study demonstrates that a novel memory training course significantly enhances memory abilities in students facing learning challenges. Notable improvements were seen in several memory functions, regardless of gender differences. The findings suggest several potential applications and the feasibility of incorporating cognitive training interventions into educational strategies to provide academic support for youngsters facing learning disabilities.